Speech and thought representation in Si Duglit, ang dugong makulit: A story that indigenizes universal scientific principles for children - Estacio, Ma. Joahna Mante (Animo Repository, 2011)
Writers of stories for children often suggest that narratives for this group of readers should be simple in both content and in structure. This paper focuses on the structure of children's stories, particularly on speech and thought representation to understand how an author's conscious and unconscious choices on who will say what lines, and how these lines will be expressed in the stories will elicit certain effect on the readers. Moreover, this stylistics paper describes the overall effect of the writer's use of the various modes of representation: making the story engaging to the readers by appealing to their senses and emotions and by making the characters interact with one another on one hand (mimesis or 'showing'), and on the other, making the story far and distant to the readers by revealing most of the information in the story through straight narration from the author's point of view (digesis or 'telling'). An interesting type of story to study in terms of its speech and thought representation is stories for children because the intended readers of these stories are persons who have yet to develop all the reading and literary skills necessary to fully understand and appreciate literature in general and stories in particular. In addition, there are modern children's stories that attempt to explain universal scientific principles through imaginative and indigenous stories for children which this researcher argues to be more challenging to comprehend than the typical and traditional stories for children. This research further engages the readers to reflect on the possible pedagogical implications of the findings which generally establish the presence of various categories of speech and thought representation in this type of stories when read by young bilingual readers.